The impact of type 2 diabetes on left ventricular function in hypertensive patients: a three-dimensional speckle-tracking imaging study - Yang Qingmei; Chen Xiaoyan; Fang Jianxiu (Frontiers in Cardiovascular Medicine)
ObjectivesThe study aimed to evaluate the impact of the co-occurrence of hypertension and type 2 diabetes mellitus (T2DM) on the deterioration of left ventricular (LV) structure and function using three-dimensional speckle-tracking imaging (3D-STI), compared to patients with only hypertension.MethodsData from 272 hypertensive patients, including 85 with T2DM and 187 without, along with 45 normal controls, were analyzed. Participant characteristics were assessed before and after propensity score matching (PSM). 3D-STI-derived parameters, including LV function and global strain parameters, were compared among controls and different patient groups. Multivariable linear regression analyses were conducted to determine the impacts of T2DM on LV function and global strain. Additionally, linear mixed-effects regression models were used to evaluate the associations between 3D-STI-derived parameters and T2DM over time in hypertensive patients.ResultsSignificant increases in the E/e' ratio and declines in the LV global radial strain (GRS) were observed across the control group, HTN (T2DM-) group, and HTN (T2DM+) group. After adjusting for various factors using PSM analysis, LV global circumferential strain (GCS) and global area strain (GAS) were also found to be significantly decreased in the HTN (T2DM+) group compared to the HTN (T2DM-) group. Multivariable regression analyses, accounting for various covariates, indicated that T2DM was independently linked to LV strains (LV GAS: β = 0.95, 95% CI: 0.90–1.00, p = 0.029; LV GRS: β = 1.03, 95% CI: 1.01–1.06, p = 0.014) in hypertensive patients. Furthermore, linear mixed-model analysis revealed that LV GCS (β = 1.20, 95% CI: 0.38–2.01, p = 0.004) and GRS (β = −2.82, 95% CI: −4.97–0.68, p = 0.010) deteriorated over the 12-month period.ConclusionsT2DM exacerbates the decline in LV global and regional strains in patients with hypertension, and 3D-STI may be a valuable tool for detecting these asymptomatic preclinical abnormalities.